Proceedings of the Scientific-Practical Conference "Research and Development - 2016" 2017
DOI: 10.1007/978-3-319-62870-7_51
|View full text |Cite
|
Sign up to set email alerts
|

The Technology and Setup for High-Throughput Synthesis of Endohedral Metal Fullerenes

Abstract: The article presented the technology and setup for high-throughput synthesis of carbon nanostructures. It was shown that the plasma-chemical synthesis of fullerenes and endohedral metallofullerenes (EMF) in high-frequency arc discharge can be controlled by changing helium pressure in the chamber. The methods of extraction using Lewis acids and separation of individual EMF by HPLC were suggested as the most effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Further studies in this area can help optimize the exact synthetic parameters for the desired type of fullerene. Another helium pressure-dependent study was reported by Cherviakova et al [98], where they carried out a series of experiments by keeping all the variables constant and only changing the He pressure in the chamber from 30 to 360 mBar. The experiment was carried out for various EMFs, and they found that although 120 mBar helium pressure yields the optimal condition for synthesis of different M@C 82 , there is a huge variation in the obtained optimal yield.…”
Section: Effect Of Helium Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…Further studies in this area can help optimize the exact synthetic parameters for the desired type of fullerene. Another helium pressure-dependent study was reported by Cherviakova et al [98], where they carried out a series of experiments by keeping all the variables constant and only changing the He pressure in the chamber from 30 to 360 mBar. The experiment was carried out for various EMFs, and they found that although 120 mBar helium pressure yields the optimal condition for synthesis of different M@C 82 , there is a huge variation in the obtained optimal yield.…”
Section: Effect Of Helium Pressurementioning
confidence: 99%
“…It is also important to note that different solvents work for different types of EMF. For instance, under constant parameters, Chervyakova et al [98] showed that CS 2 could efficiently extract 11 wt% of Y@C 82 out of all fullerenes, compared to 5.0 wt % and 2.3 wt% yield of Sc@C 82 and Gd@C 82 , respectively. Moreover, although CS 2 and C 5 H 5 N are both considered a good solvent for extracting EMFs, it was observed that the overall yield of M@C 82 could vary widely between the types of solvents used under different synthetic parameters.…”
Section: Solvent Extractionmentioning
confidence: 99%